2017
DOI: 10.14411/fp.2017.027
|View full text |Cite
|
Sign up to set email alerts
|

A synoptic review of Caryophyllaeus Gmelin, 1790 (Cestoda: Caryophyllidea), parasites of cyprinid fishes

Abstract: Phylogenetic interrelations of four species of the genus including its type species and newly described C. chondrostomi were assessed based on an analysis of sequences of lsrDNA and cox1. A key to identification of all valid species of Caryophyllaeus is also provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…The molecular characterization, performed in accordance with Bazsalovicsová et al (2014), based on the sequencing of 2 marker loci, allowed a precise identification of the specimens encountered in S. tenellus. This approach appeared more reliable than the morphological analysis alone, as suggested by Nadler and de León (2011), since fish Caryophyllidea species morphologically could show some plasticity (Bazsalovicsová et al, 2014;Barčák et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The molecular characterization, performed in accordance with Bazsalovicsová et al (2014), based on the sequencing of 2 marker loci, allowed a precise identification of the specimens encountered in S. tenellus. This approach appeared more reliable than the morphological analysis alone, as suggested by Nadler and de León (2011), since fish Caryophyllidea species morphologically could show some plasticity (Bazsalovicsová et al, 2014;Barčák et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…(2014), based on the sequencing of 2 marker loci, allowed a precise identification of the specimens encountered in S. tenellus . This approach appeared more reliable than the morphological analysis alone, as suggested by Nadler and de León (2011), since fish Caryophyllidea species morphologically could show some plasticity (Bazsalovicsová et al ., 2014; Barčák et al ., 2017). Our molecular data revealed that the tapeworms belong to C. brachycollis species; thus the current study is the first study on type-host ( S. tenellus ) and type-locality (Lake Blidinje, Bosnia-Herzegovina) for this parasite.…”
Section: Discussionmentioning
confidence: 99%